In vitro compatibility and stability of admixtures containing etoposide, epirubicin hydrochloride and vindesine sulphate in a single infusion bag. (17th September 2019) - Li, Jiafei; Yao, Chong; Xu, Yanping; Ping, Ping; Yin, Hong; Sun, Yan
Abstract: What is known and objectives: The etoposide, doxorubicin hydrochloride, vincristine sulphate, cyclophosphamide and prednisone (EPOCH) chemotherapy regimen is effective in patients with relapsed or refractory non‐Hodgkin's lymphoma. However, vincristine and doxorubicin hydrochloride are relatively toxic, leading to neurovirulence and cardiotoxicity, respectively. In this study, we replaced these drugs with vindesine and epirubicin hydrochloride to reduce the cardiotoxicity and evaluated admixtures containing these drugs along with etoposide in a single infusion bag in vitro. Methods: The appearance and pH of the admixtures were evaluated, and the number of particles was detected. High‐performance liquid chromatography was used to measure the concentration and degradation rates of etoposide, epirubicin hydrochloride and vindesine sulphate in each admixture. Results and discussion: No precipitation occurred when mixing clinically relevant concentrations of etoposide, epirubicin hydrochloride and vindesine sulphate in a 0.9% NaCl injection solution. Furthermore, the delta pH of the admixtures was ≤0.12 throughout the experiment, and the number of particles (≥10 and ≥25 μm) in the solutions over the 24 hours post‐preparation period met USP standards. Etoposide, epirubicin hydrochloride and vindesine sulphate were retained at >96% of their initial concentrations in the admixtures at 25°C over the course of the experiment. Etoposide, epirubicin hydrochloride and vindesine sulphate are compatible when mixed in a 0.9% NaCl injection solution, and the admixtures are stable for at least 24 hours when stored in infusion bags. What is new and conclusion: This in vitro analysis indicates the suitability of our novel admixtures containing less toxic drug equivalents in a single infusion bag for clinical application.